2011
DOI: 10.15288/jsad.2011.72.555
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Style and Dating Violence in a Sample of Urban, Alcohol-Using Youth

Abstract: ABSTRACT. Objective: This study examined childhood abuse, problem behavior, drinking style, and dating violence (DV). Our goal was to assess whether (a) alcohol use-related beliefs and behaviors ("drinking style") would be associated with DV perpetration and victimization, (b) drinking style would mediate the relationship between childhood abuse and DV, and (c) the drinking style-DV relationship would be attributable to propensity for problem behavior. Method: Cross-sectional survey data were collected from 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 53 publications
1
22
0
1
Order By: Relevance
“…It has been proposed that alcohol use creates a myopic effect, facilitating aggressive behavior due to an increased focus on negative, aggressive cues while intoxicated (Chermack & Giancola, 1997; Giancola, 2002; Steele & Josephs, 1990). In recent years, there has been a wealth of research on the relation between alcohol use and aggression against intimate partners (e.g., Foran & Oā€™Leary, 2008; Rothman et al, 2011; Shorey, Stuart, & Cornelius, 2011; Stuart, Oā€™Farrell, & Temple, 2009), with findings generally demonstrating that alcohol use is positively associated with aggression against an intimate partner. However, continued research is needed on the relation between alcohol use and aggression against intimate partners, particularly among populations known to be at high risk for both alcohol consumption and aggressive behavior.…”
mentioning
confidence: 99%
“…It has been proposed that alcohol use creates a myopic effect, facilitating aggressive behavior due to an increased focus on negative, aggressive cues while intoxicated (Chermack & Giancola, 1997; Giancola, 2002; Steele & Josephs, 1990). In recent years, there has been a wealth of research on the relation between alcohol use and aggression against intimate partners (e.g., Foran & Oā€™Leary, 2008; Rothman et al, 2011; Shorey, Stuart, & Cornelius, 2011; Stuart, Oā€™Farrell, & Temple, 2009), with findings generally demonstrating that alcohol use is positively associated with aggression against an intimate partner. However, continued research is needed on the relation between alcohol use and aggression against intimate partners, particularly among populations known to be at high risk for both alcohol consumption and aggressive behavior.…”
mentioning
confidence: 99%
“…The other five scales that have been developed specifically to measure dating violence among adolescents are the Psychological Abuse Index (PAI; Molidor, 1995), the Safe Dates Psychological and Physical Dating Abuse Scales (Safe Dates; Foshee et al, 1996), the Conflict in Adolescent Dating Relationship Inventory (CADRI; Wolfe et al, 2001), the Date and Family Violence and Abuse Scale (DFVAS; Symons, Groer, Kepler-Youngblood, & Slater, 1994), and the Dating Violence Perpetration Acts Scale (DVPAS; Rothman et al, 2011, 2012). The DVPAS captures all forms of adolescent dating violence (physical, psychological, sexual, stalking, and electronic), and the majority of the other measures (Safe Dates, CADRI, DFVAS) assess physical, psychological, and sexual dating violence.…”
Section: This Studymentioning
confidence: 99%
“…For instance, disruptions in cognitive processes, irrational behavior, increased arousal, and a reduction in the inhibition of aggressive impulses may all contribute to increased violence (Chermack & Giancola, 1997; Ito, Miller, & Pollock, 1996; Pihl & Peterson, 1995; Virkkunen & Linnoila, 1993). Numerous studies have indicated strong associations between violence (victimization and aggression) and alcohol use (Rothman et al, 2011; Swahn and Donovan, 2006; Swahn et al, 2004) and/or drug use among youth (Cunningham et al, 2006, Epstein-Ngo et al, 2012; White et al, 2012,Walton et al, 2009). The National Survey on Drug Use and Health, for example, indicated that youth who used any illicit drug in the past year were almost twice as likely to have engaged in violence compared to youth who did not report use of illicit drugs (SAHMSA, 2006).…”
Section: Introductionmentioning
confidence: 99%